Tribology and applications of self-lubricating materials - Omrani, Emad; Rohatgi, P. K.; Menezes, Pradeep L. (CRC Press, Taylor & Francis Group, 2018)
This book emphasizes an understanding of the tribological nature of different composites such as metal, polymer, and ceramic matrix composites and discusses the compatibility of these composites with specific lubricants. The book also offers a view of advancements in the development of self-lubricating mechanisms and covers the latest technologies in the field.